A Site-Ordered Quadruple Perovskites, RMn3Ni2Mn2O12 with R = Bi, Ce, and Ho, with Different Degrees of B Site Ordering - Alexei A. Belik (Molecules)
A site-ordered quadruple perovskites, AA′3B4O12, can have 3d transition metals at A′ and B sites, and show complex magnetic interactions and behavior. Additional complexity appears when B site-ordered arrangements are realized in AA′3B2B′2O12. In this work, A site-ordered quadruple perovskites, RMn3Ni2Mn2O12 with R = Bi, Ce, and Ho, were prepared by a high-pressure, high-temperature method at about 6 GPa and about 1500 K. The R = Bi and Ce samples were found to crystallize in space group Im-3 with a disordered distribution of Ni2+ and Mn4+ cations in one B site. On the other hand, the R = Ho sample crystallized in space group Pn-3 and showed partial ordering of Ni2+ and Mn4+ cations between two B sites. The structural data (and bond valence sums) suggest that cerium has the oxidation state +3, which is unusual for such perovskites. Magnetic properties were investigated by magnetic susceptibility and specific heat measurements, which showed the presence of one magnetic transition near 36 K for R = Bi; there was evidence for the presence of two magnetic transitions near 27 K and 33 K for R = Ce, and near 10 K and 36 K for R = Ho. Curie–Weiss parameters were estimated for all samples from high-temperature magnetic measurements up to 750 K. The total effective magnetic moment for R = Ce also suggests the presence of Ce3+. A magnetic field of 90 kOe had the largest effect on the specific heat of the R = Ho sample, and almost no effects on the specific heat of the R = Bi sample.